Competition in the Labor Market: The Wage Effect of Employer Concentration in China - Jianan Liu; Hongbo Cai; Carl Lin (Institute of Labor Economics (IZA), 2024)
Competition in the labor market theoretically leads to higher wages, yet empirical evidence to substantiate it, particularly in developing countries, has been sparse. Our study delves into the impact of increased competition in the labor market on workers' wages using a panel dataset from Chinese industrial firms spanning 1998 to 2013. Employing OLS and IV regressions, we demonstrate that a decrease in employer concentration is significantly linked to higher wages. The elasticities of employer concentration on wages fall within the range of -0.034 and -0.107. Additionally, our findings suggest that state-owned enterprises gained the most from this upswing in competition, primarily due to restructuring. Furthermore, we demonstrate that total factor productivity serves as an important channel linking employer concentration to wages.
Keywords: J42; J3; O53; 330; labor market concentration; monopsony; competition; wages; China